"MODELAGEM PREDITIVA, AVALIAÇÃO E VALORAÇÃO DE SERVIÇOS ECOSSISTÊMICOS DE ESTOQUE E SEQUESTRO DE CARBONO NA BACIA HIDROGRÁFICA DO CÓRREGO BEBEDOURO, MATO GROSSO DO SUL, BRASIL. - Bruna Dienifer Souza Sampaio (2023)
Ecosystem services (ES) are defined as all the direct and indirect benefits that the human population obtains from nature. The economic system is heavily dependent on the flow of goods and services, which, with growing demand, increases pressure on natural resources, affecting the dynamic capacity of ecosystems to offer ecosystem services. Transformations in land use and coverage through the processes of converting native vegetation into agricultural production areas, intensify the exploitation of natural resources – the main drivers of environmental degradation, in a way that alters the flow of ecosystem services. The Cerrado biome is considered a biodiversity hotspot, it serves as a reservoir or “sponge”, which distributes water to other biomes, in addition to being the birthplace of springs in some of the largest basins in South America. The Cerrado provides comprehensive ecosystem services such as: water supply through surface runoff, groundwater recharge and atmospheric water vapor fluxes; storing large amounts of carbon in its forests, especially in the deep roots of trees; high biodiversity in order to offer resources to sustain the lives of family farmers. The State of Mato Grosso do Sul stands out in the policy of expanding agricultural areas, with a diversified production in agribusiness/agroindustry, supplying products such as sugar cane, corn, iron ore, cattle/meat, soybeans and emphasis on the production of paper and cellulose, which in turn has intensified the process of transformation in the landscape. The Cerrado biome is being threatened due to human activities, with emphasis on livestock, forestry and the reduction of native vegetation. Cerrado vegetation fragments constitute carbon sinks and play an important role in mitigating climate change. This occurs because, after being removed from the atmosphere, carbon accumulates in plants and soil. However, the conversion of savanna-forest formation to other types of use and coverage can release large amounts of carbon dioxide (CO2) into the atmosphere. Thus, transformations in land use and cover are important factors that affect the provision of ecosystem services. The quantification, mapping and evaluation of these services play an essential role in strategies aimed at environmental conservation. The general objective of this thesis was to estimate the ecosystem services resulting from carbon stock and sequestration in current and conservationist change trend scenarios in the Córrego Bebedouro (MS) watershed, located between the municipalities of Três Lagoas and Selvíria (MS), where is the driving industry for the production of paper and cellulose. The methodology consisted of using remote sensing and geoprocessing techniques, through digital processing of images from Landsat 5/TM and Landsat 8/OLI sensors and use of the Google Earth Engine (GEE) platform in JavaScript language, using a classifier algorithm based on Random Forest (RF) decision tree. Spatio-temporal changes (1984, 2004, 2009, 2015 and 2021) in land use and cover were analyzed, and predictive modeling was used to estimate carbon sequestration in 2033 and 2051 in different scenarios. The following classes were defined: water, alluvial vegetation, savanna-forest formation, pasture, forestry and built areas. Supervised classification and identification of the main changes to land use and cover that occurred during the temporal analysis were carried out. To validate the classification, the ENVI software was used and the global accuracy and Kappa index were estimated, in addition to the ArcGIS software for editing and quantifying the classification. The data were correlated through cross-tabulation and area calculations. The results demonstrate that the RF algorithm was a satisfactory classifier with a Kappa index ranging from 0.88 (1984) to 0.96 (2021). There were changes in land use and coverage, primarily with the replacement of savanna-forest formation (Cerrado vegetation) for pasture and fragmentation of Cerrado areas. Subsequently, pasture areas were replaced by eucalyptus cultivation, with the vast majority of these areas destined for cellulose production. The historical projection for the BAU scenario indicates that 35% of the area (2033) and approximately 38% (2051) of the river basin area will be forestry. However, for the conservation scenario (PF), it points to a percentage increase in area in the alluvial vegetation class from 10.2% (2021) to 11.52% (2033) and 11.86% (2051). It is concluded that in the conservationist scenario the valuation of ecosystem services has twice the carbon sequestration, and consequently, gains in relation to the net present value of C when compared to the current trend scenario.